Kepemimpinan Perempuan dalam Surah An-Nisa': (34): Impelementasi Makna Ma’na Cum Maughza Sahiron Syamsuddin - Khoirin Ni’mah; Delta Yaumin Nahri; Atiqullah Atiqullah; Faris Syariful Hikam (Jurnal Budi Pekerti Agama Islam, 2025)
The aim of this research is to find out the hermeneutics in the approach used by Sahiron Syamsuddin with the term ma’na cum maghza theory in the analysis of leadership in contemporary history. This research is an application of a quantitave approach, because it comes from several reference sources such as books, journals and articles. The results of this research are to develop knowladge and find out the contets of the verses used in a text and the context to understand the interpretations of the verses of the Qur’an so that reinterpretations can be made to understand the analysis of Qs. An-nisa: 34 in Sahiron Syamsuddin’s hermeneutics.